Early Holocene woodland vegetation and human impacts in the arid zone of the southern Levant. (October 2015) - Asouti, Eleni; Kabukcu, Ceren; White, Chantel E; Kuijt, Ian; Finlayson, Bill; Makarewicz, Cheryl
Palynological archives dating from the Pleistocene–Holocene transition are scarce in the arid zone of the southern Levant. Anthracological remains (the carbonized residues of wood fuel use found in archaeological habitation sites) provide an alternative source of information about past vegetation. This paper discusses new and previously available anthracological datasets retrieved from excavated habitation sites in the southern Levant dating to the Pre-Pottery Neolithic (PPN) period. The available evidence indicates the existence of distinct arboreal floras growing in different ecological niches, which occupied areas that today are either treeless or very sparsely wooded. The anthracological data provide independent confirmation of the hypothesis that early Holocene climate in the southern Levant was significantly moister than at present. Clear North–South and East–West precipitation and associated woodland composition gradients are evidenced. Far from deducing widespread anthropogenic degradation of the regional vegetation, it is suggested that woodland expansion in the semi-arid interiors of the Levant may be attributed to the intensive management of Pistacia woodlands for food, fuel and pasture.